Effect of agro-ecosystem and periods of the year upon earthworm population density on silvopastoral systems - Benavides, H. R.; Vargas, S.; Caicedo, D.; Carvajal, L.; Gutiérrez, D. I.; Mina, J. (Cuban Journal of Agricultural Science, 2019)
A completely randomized design with three treatments (agroecosystems): A1 (grasses and Alnus acuminata Kunth); A2 (grasses and Acacia melanoxylon R. Br.) and A3 (Grassland) and four periods of the years (PY): 1-12-2015 (1); 1-6-2016 (2); 1-12-2016 (3) and 1-6-2017 (4) in a factorial analysis was conducted to evaluate the effects of agro-ecosystems (AES) and periods of the years upon the earthworm population density (EPD). There was not interaction (p>0.001) between AES and PY upon the EPD. The agro ecosystem A1 (189 m-2) differed (p<0.001) from A2 and A3 with (117 and 128 m-2) while these were similar in earthworms. The periods of the years effect (p<0.001) upon the EPD was higher in PY1 and PY2 (157 and 188 m-2) without differences between them, meanwhile the PY3 and PY4 were similar (118 and 116 m-2) but differed from the previous periods. The best results in the response variable was achieved in A1 agro-ecosystem which coincided with the better forestry indicators with a mean difference of 1.66 m and 5.84 cm, in height and diameter, respectively. The survival of earthworms and its population density in all agro-ecosystems and periods of the years suggested that EPD is an appropriate bio-indicator to assess the soil health in agroforestry systems and grasslands, closely related with the edaphoclimatic conditions, design and management. Keywords: agroforestry, soil biota, grassland